Atypical Glutaric Aciduria Type I with Hemidystonia and Asymmetric Radiological Findings Misdiagnosed as an Ischemic Stroke. Issue 4 (19th July 2018) - Demailly, Diane; Vianey‐Saban, Christine; Acquaviva, Cécile; Gonzalez, Victoria; Rubio, Isabel De Antonio; Cyprien, Fabienne; Roujeau, Thomas; Masoliver, Adria; Leboucq, Nicolas; Coubes, Philippe; Cif, Laura
Abstract : View Supplementary Video 1